Implementación de un sistema básico de gestión administrativo y financiero en la liga deportiva intercomunal “ANGAHUANA BAJO” de la provincia de Tungurahua cantón Ambato parroquia Santa Rosa. - Agualongo Yugcha, Juan Carlos (2019)
The present integrative project arose from the need to have the systematized information of reliable administrative and financial management in the “Angahuana Bajo inter-communal sports league of the Tungurahua province of the canton Ambato in Santa Rosa parish, since it does not have systematized information, it takes time to publicize the financial results since in some cases the documentation is not in order, generating insecurity in the activities that the league executes mainly in decision making. For which it is important to have a basic system of administrative and financial management, which allows to control all the activities that are carried out in the matches of football matches on weekends within each sports scenario, allowing the administration to improve financial that is carried out in an orderly manner and complying with the proper performance of all operations carried out in accordance with the rules and principles, allowing the institution to have no problems with the different Regulation and Control bodies in the future; in this way contribute to the fulfillment of the institutional objectives, helping the administration to make timely and correct decisions. The present integrating project, aims to improve the reports of the financial results and to an order of the administration, for the realization of the project, an investigative method has been used that allows the collection of information in the organization, the technique used, was the surveys to all the members of the board, and the presidents of the participating clubs, in order to obtain necessary and important information for the development of the project, orienting to a design of a systematized system, that allows to know the utility generated by the sports league inter-communal whereby this system will help with tools and therefore with a quality administration, improving the performance of the person in charge in each function as a leader who will be able to fulfill each function, will be able to make decisions regarding the incentives to the teams finalists, handling in a better way the strategies of Increase more teams participating in the league. The administrative management system that is proposed, is designed in a free software called PHP, with data in MySQL, it is easy to use it is not necessary to have internet for the operation this allows to manipulate different modules that in this case is divided into two parts the administrative part and the financial part.